A new approach of fatigue life prediction for metallic materials under multiaxial loading. (September 2015) - Li, B.C.; Jiang, C.; Han, X.; Li, Y.
Highlights: The effects of stress amplitude ratio and stress level have been discussed. Multiaxial fatigue life surface has been proposed. A new path-dependent factor has been presented. A new approach to predict fatigue life has been introduced. The numerical calculation procedure for life prediction has been given. Abstract: Based on experimental data found in literatures, four traditionally multiaxial fatigue life criteria are analyzed and verified. It is discovered that these conventional criteria cannot reflect well the combined effect both under tension and torsion loadings for some materials, such as 6082-T6 and AlCu4Mg1, due to lack of enough consideration about the influence of stress amplitude ratio and stress level on fatigue life even under proportional loading. In order to solve this problem, a new approach of fatigue life prediction, based on the equal-life curve, is proposed and it is composed of three parts: the multiaxial fatigue life surface, a new path-dependent factor for multiaxial high-cycle fatigue and a material parameter describing material sensitivity to non-proportional loading. Finally, the precision of the presented approach is systematically checked against the experimental data found in literatures for four different materials under proportional and non-proportional loadings.